2010
DOI: 10.1111/j.1365-2702.2008.02767.x
|View full text |Cite
|
Sign up to set email alerts
|

Thinking ‘taller’: sharing responsibility in the everyday lives of children with asthma

Abstract: Some parents would like more assistance from health professionals in managing the process of increasing independent self-care by children. It is important to maintenance of the health of children with long-term conditions that the distribution of responsibilities between adults and children both ensures children's safety and provides appropriate preparation for independence in adult life. Understanding the process by which parents and children negotiate distribution of responsibilities for long-term conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 14 publications
(23 reference statements)
3
62
0
Order By: Relevance
“…The findings illustrated that a child of seven years of age has the ability to make autonomous management decisions, for example understanding his asthma symptoms will reduce if he modified his running pace. These findings resonate with previous research undertaken with children of a similar age that also demonstrated autonomous decision-making skills to reduce asthma symptoms through the reduction or avoidance of asthma triggers (Meah et al, 2009) …”
Section: Conceptual Frameworksupporting
confidence: 89%
“…The findings illustrated that a child of seven years of age has the ability to make autonomous management decisions, for example understanding his asthma symptoms will reduce if he modified his running pace. These findings resonate with previous research undertaken with children of a similar age that also demonstrated autonomous decision-making skills to reduce asthma symptoms through the reduction or avoidance of asthma triggers (Meah et al, 2009) …”
Section: Conceptual Frameworksupporting
confidence: 89%
“…Working in partnership with parents, as well as young people, will likely lead to a smoother and more effective transition for all. However, despite acknowledgement of the need for parent-targeted transition support [10,55,62] Allen et al [28] highlight that provision for parents is withdrawn at the time they need it most. Intervention studies remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this review is that even though our definition of young people was broad, searches still identified papers discussing healthcare transition from the perspective of parents of children who fell outside of our specified age range [e.g. 62,75] and papers in which the parental perspective could not be distinguished from that of young people or professionals [e.g. 76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Parents take more responsibility in disease management in the early years. However, if they take more responsibility in later years, it becomes more difficult for children to gain independence (Meah, Callery, Milnes, & Rogers, ). Parents should encourage their children to take responsibility after the development of their cognitive and psychomotor skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, these responsibilities should be identified clearly (Buford, ; Orrell‐Valente et al., ; Riley, ). During the transition period, nursing support, guidance, and monitoring are part of good clinical management of asthma (Meah et al., ). Additionally, nursing support is necessary in the transition period to prevent discord between children and parents (Ekim & Pek, ; McQuaid et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%